2022
DOI: 10.1038/s42005-022-01021-y
|View full text |Cite
|
Sign up to set email alerts
|

Engineering non-Hermitian skin effect with band topology in ultracold gases

Abstract: Non-Hermitian skin effect(NHSE) describes a unique non-Hermitian phenomenon that all eigen-modes are localized near the boundary, and has profound impact on a wide range of bulk properties. In particular, topological systems with NHSE have stimulated extensive research interests recently, given the fresh theoretical and experimental challenges therein. Here we propose a readily implementable scheme for achieving NHSE with band topology in ultracold gases. Specifically, the scheme realizes the one-dimensional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…There exist several physical incarnations that can be used to explore the non-Hermitian systems [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] , including the cold atoms [48][49][50][51] , electrical circuits [52][53][54][55][56][57] , photonic and acoustic systems [58][59][60][61][62] . Among them, electric circuits have been widely used because the circuit structure can be flexibly designed to facilitate integration and mass production.…”
Section: Experimental Implementationmentioning
confidence: 99%
“…There exist several physical incarnations that can be used to explore the non-Hermitian systems [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] , including the cold atoms [48][49][50][51] , electrical circuits [52][53][54][55][56][57] , photonic and acoustic systems [58][59][60][61][62] . Among them, electric circuits have been widely used because the circuit structure can be flexibly designed to facilitate integration and mass production.…”
Section: Experimental Implementationmentioning
confidence: 99%
“…While the excellent tunability of Raman lattices provides access to a plethora of dynamic topological phenomena either in quench processes or periodically-driven Floquet settings [8][9][10], a largely unexplored possibility is the further introduction of dissipation. A dissipative Raman lattice should exhibit even more exotic properties in the highly non-trivial context of quantum open systems [11]. This is expected, since dissipation has been shown to stabilize interesting manybody phases [12][13][14] or phase transitions [15][16][17][18][19] under the framework of quantum master equation.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Hermitian parity-time (PT ) symmetry physics has experienced rapid developments in the last two decades, especially in the field of optics, where the balanced optical gain and loss can be modeled by a PT -symmetric Hamiltonian, and it is found that gain and loss can serve as new engineering tools and also lead to abundant new and unexpected features [34][35][36][37][38]. These great developments inspired the interest in extending cold atom physics from Hermitian to non-Hermitian regime, with the prospect of exploring unidirectional transportation [39], non-Hermitian skin effect [40][41][42][43], soliton [44][45][46], double-well [47][48][49] and Hubbard model [50,51] in open environments, etc. In cold atom systems, controlled atomic loss can be realized by extracting atoms from the atomic gas via atom-light interaction [52]; while the atomic gain is proposed to be realized by injecting atoms into the atomic gas using an atom laser [53].…”
Section: Introductionmentioning
confidence: 99%